Climatic Aridity Gradient Modulates the Diversity of the Rhizosphere and Endosphere Bacterial Microbiomes of Opuntia ficus-indica - Karray, Fatma; Gargouri, Mahmoud; Chebaane, Asma; Mhiri, Najla; Mliki, Ahmed; Sayadi, Sami (Frontiers in Microbiology, 2020)
Recent microbiome research has shown that soil fertility, plant-associated microbiome and crop production can be affected by abiotic environmental parameters. The effect of aridity gradient on rhizosphere-soil (rhizosphere) and endosphere-root (endosphere) prokaryotic structure and diversity associated with Cacti remain poorly investigated and understood. In the current study, next-generation sequencing approaches were used to characterize the diversity and composition of bacteria and archaea associated with the rhizosphere and endosphere of Opuntia ficus-indica spineless cacti in four bioclimatic zones (humid, semi-arid, upper-arid and lower-arid) in Tunisia. Our findings showed that bacterial and archaeal cactus microbiomes changed in inside and outside roots and along the aridity gradient. Plant compartement and aridity gradient were the influencing factors on the differentiation of microbial communities in rhizosphere and endosphere samples. The co-occurrence correlations between increased and decreased OTUs in rhizosphere and endosphere samples, and soil parameters were determined according to the aridity gradient. Blastococcus, Geodermatophilus, Pseudonocardia, Promicromonospora and Sphingomonas were identified as prevailing hubs and were considered as specific biomarkers taxa which could play a crucial role on the aridity stress. Overall, our findings highlighted the prominence of the climatic aridity gradient on the equilibrium and diversity of microbial community composition in rhizosphere and endosphere of cactus.